Results of experiments of hydrothermal alteration of Middle Valley sediment from ODP Hole 139-855A - Anna M Cruse; Jeffrey S Seewald (PANGAEA, 2001)
The presence of sedimentary organic matter blanketing midocean ridge crests has a potentially strong impact on metal transport in hydrothermal vent fluids. To constrain the role of organic matter in metal mobility during hydrothermal sediment alteration, we reacted organic-rich diatomaceous ooze from Guaymas Basin, Gulf of California, and organic-poor hemipelagic mud from Middle Valley, northern Juan de Fuca Ridge, with seawater and a Na-Ca-K-Cl fluid of seawater chlorinity, at 275° to 400°C, 350 to 500 bars, and initial fluid: sediment mass ratios ranging from 1.6 to 9.8. Reaction of these fluids with both sediment types released CO2 and high concentrations of ore-forming metals (Fe, Mn, Zn, Pb) to solution. Relatively low concentrations of Cu were observed in solution and likely reflect the reducing conditions that resulted from the presence of sedimentary organic matter. Both the concentrations of CO2 and dissolved metals were lower in fluids reacted with Middle Valley sediment compared with aqueous concentrations in fluids reacted with Guaymas Basin sediment. During alteration of both sediment types, metal concentrations varied strongly as a function of temperature, increasing by up to an order of magnitude over the 75°C range of each experiment. Major element fluid chemistry and observed alteration assemblages suggest that during hydrothermal alteration of organic-lean sediment from Middle Valley a feldspar-quartz-illite mineral assemblage buffered in situ pH. In contrast, data from the experimental alteration of organic-rich Guaymas Basin sediment suggest that a calcite-plagioclase-quartz assemblage regulated in situ pH. Fluid speciation calculations suggest that in situ pH during Guaymas Basin sediment alteration was lower than during alteration of Middle Valley sediment and accounts for the substantially greater metal mobility at a given temperature and pressure during the former experiment. Comparison of our results with the results of basalt alteration experiments indicate that except for Cu, hydrothermal sediment alteration results in equal or greater concentrations of ore-forming metals at a given temperature and pressure. Accordingly, the presence of ore-forming metals in fluids currently venting from sediment-covered hydrothermal systems at concentrations substantially lower than in fluids from bare-rock systems may reflect chemical reequilibration during subsurface cooling within the sediment pile.
Supplement to: Cruse, AM; Seewald, JS (2001): Metal mobility in sediment-covered ridge-crest hydrothermal systems: Experimental and theoretical constraints. Geochimica et Cosmochimica Acta, 65(19), 3233-3247, https://doi.org/10.1016/S0016-7037(01)00660-3